2021
DOI: 10.1038/s41598-021-97595-8
|View full text |Cite
|
Sign up to set email alerts
|

Upward trends in new, rifampicin-resistant and concurrent extrapulmonary tuberculosis cases in northern Guizhou Province of China

Abstract: Similar to global trends, the incidence rate of tuberculosis (TB) in China declined from 2000 to 2018. In this study, we aimed to evaluate TB trends in northern Guizhou Province and identify risk factors associated with rifampicin-resistant (RR) and concurrent extrapulmonary TB (EPTB). We analyzed data of TB patients hospitalized in Affiliated Hospital of Zunyi Medical University from 2011 to 2018, and assessed correlations between demographic characteristics of patients and RR-TB as well as concurrent EPTB. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One study indicated that the prevalence of smear-positive TB in China decreased from 170/100 000 population in 1990 to 59 /100 000 population in 2010, a reduction of more than 50 percent[ 15 ]. Despite past success in controlling TB, the limited epidemiologic information available suggests that the incidence of EPTB may be increasing steadily worldwide, including in China[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that the prevalence of smear-positive TB in China decreased from 170/100 000 population in 1990 to 59 /100 000 population in 2010, a reduction of more than 50 percent[ 15 ]. Despite past success in controlling TB, the limited epidemiologic information available suggests that the incidence of EPTB may be increasing steadily worldwide, including in China[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of economic development and health resources may also have an impact on the drug resistance rates in various regions. 4 , 21 , 22 For example, in Hangzhou and Ningbo, due to their developed economies and abundant health resources, the local population tend to be highly mobile, rich in social interactions, and complex in interpersonal activities, which may lead to rifampicin resistance rates at high levels. Even so, the rate of drug resistance in each municipality was decreasing year by year, and the province was on a steady downward trend.…”
Section: Discussionmentioning
confidence: 99%
“…The TB epidemic status crucially depends on regional geographic, socioeconomic, and cultural variations. 4 Therefore, the prevalence of tuberculosis in different regions also varies. For example, in Shandong Province in northern China, the rifampicin-resistance rate in newly diagnosed tuberculosis cases was 4.43%, while the rifampicin-resistance rate in retreated patients was 11.26%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and clinical data of patients were collected. The data collection and procedures were described previously ( 4 ). Any information related to patient identity was filtered to ensure the data used in this study were anonymous.…”
Section: Methodsmentioning
confidence: 99%